Trincas em sedes de plugue para panelas de aço: estudo de caso em unidade industrial - Ribeiro, Gabriela Bugni (Universidade Federal de São Carlos, 2022)
Purging blocks are important components located in the bottom of Steel Ladles. Its main objective is to protect and connect the ladle and the plug, throughout inert gas, usually argon, is injected into the liquid metal bath. Such components generally suffer with constant chemical and physical solicitation, which requires properties as high resistance to corrosion and thermal shock to be able to operate as required. Due to these solicitations, it is important that, during the production of the purging blocks, defects are minimized, such as micro cracks, which reduce their useful life and even make their use unfeasible. During the manufacture of purging blocks at the Monolithic and Pre-Molded Factory (FMPM) of RHI Magnesita located in Contagem-MG, several specimens began to present cracks after the drying stage, being discarded for not attend the required quality standard. This study aims to understand the cause and effect of the appearance of these cracks, as well as changing the calcium aluminate-based binder and the additives used in the concret production for the purging blocks, to propose a solution to this problem, avoiding the waste of raw materials and optimizing the production process of these strategic components for the steel industry.
Cracks in purging refractory blocks for steel ladles
Keywords: Cerâmicas; Refratários; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA